2014
DOI: 10.3347/kjp.2014.52.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Clonorchiasis among Residents of Riverside Areas in Muju-gun, Jeollabuk-do, Korea

Abstract: We evaluated the status of Clonorchis sinensis infection and potential risk factors among residents of riverside areas (Geumgang) in Muju-gun, Jeollabuk-do (Province), Korea. From January to February 2010, a total of 349 (171 males, 178 females) stool samples were collected and examined by the formalin-ether concentration technique. Also, village residents were interviewed using questionnaires to obtain information about C. sinensis infection-related risk factors. Overall egg-positive rate of C. sinensis was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
6
18
0
Order By: Relevance
“…Some earlier studies have shown higher infection rates for males compared to females [11, 18, 19]. Our study corroborated these results finding that 22.27% male and 11.4% female participants were infected with the C. sinensis (P=0.001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Some earlier studies have shown higher infection rates for males compared to females [11, 18, 19]. Our study corroborated these results finding that 22.27% male and 11.4% female participants were infected with the C. sinensis (P=0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were shown in other studies [18, 21]. In the cross-sectional study conducted in Keollabuk province, Korea by [19], the rates of drinking in men and women were 56.1% and 20.8% respectively. They also found that more men ate raw fish than women (77.2% versus 46.6%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…6 In addition, the metacercariae of C. sinensis are mucilaginous in nature and can result in indirect transmission of C. sinensis through cooking utensils. 7,8 Therefore, infection can also occur occasionally in people who have never lived in endemic areas or in those who have never consumed raw freshwater fish.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey, 4.5% of the participants with C. sinensis infection did not have any history of raw fish ingestion and the discrepancy was attributed to either under-reporting or the possibility of cross-contamination from utensils 6. In recent survey data, indirect infection rates of C. sinensis were higher in women than in men in endemic and non-endemic areas (61.5% vs. 45.0% and 75% vs. 35.7%, respectively),10 which was attributed to the possibility of cross-contamination during the cooking process 7. C. sinensis infection is most serious in elderly people aged 40-60 years,11 C. sinensis infection does not result in the development of a protective immunity in cases of repeated A B C Round filling defect (A, arrows) in a dilated common bile duct on endoscopic retrograde cholangiopancreatography revealed an adult worm of Clonorchis sinensis (B, arrow).…”
mentioning
confidence: 97%